Strategi Pengelolaan Badan Usaha Milik Desa (BUMDes) dalam Pemberdayaan Masyarakat di Desa Kolam Kabupaten Deli Serdang - Dewi Khairani; Dara Aisyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Village-Owned Enterprises (BUMDes) are strategic instruments used by both central and local government to advance community empowerment and village self-reliance. This study analyzes the management of BUMDes Karya Bersama in Kolam Village, Percut Sei Tuan District, Deli Serdang Regency, with reference to the six management principles set out in Regulation of the Minister of Villages, Development of Disadvantaged Regions, and Transmigration Number 3 of 2021, namely cooperative, participatory, emancipatory, transparent, accountable, and sustainable, and examines the internal and external factors shaping their application. A descriptive qualitative approach was used, with data gathered through in-depth interviews, participant observation, and documentation, then analyzed using the Miles and Huberman interactive model, while internal and external factors were mapped through a SWOT matrix. The findings show that implementation of the six principles remains uneven: cooperation and participation are confined to a small circle of livestock farmers who supply raw material, transparency and accountability are constrained by manual and centralized bookkeeping, and sustainability is hindered by unresolved business licensing and a rented production site. Drawing on the SWOT matrix, four strategy groups are proposed, covering optimization of village-fund allocation, digitalization of administration, intensified farmer education, and expanded community outreach and digital marketing. These findings provide practical direction for strengthening BUMDes governance as an instrument of village community empowerment.